(untitled) (Research, Society and Development, 2020)
The aim of this article is to investigate the role of the elderly companion during hospitalization. This is an integrative review carried out using the databases VHL, CAPES, ScIELO, and PubMed. The review consisted of 24 articles. The results were presented in the form of a table and analyzed in categories. After analysis, two categories were chosen: role and profile of the companion; companion’s perception regarding hospitalization. There was a concern regarding the experience of the hospitalized elderly companion; others treated the elderly aspect. The importance of the presence of the companion of the elderly person during hospitalization is perceived, as this becomes part of the therapeutic process, and of the visible improvement of the elderly’s condition. It is concluded that guiding, welcoming and empowering this companion become essential actions for an effective and efficient monitoring, so that it is therapeutic and becomes an instrument for the early discharge of this patient.